Caracterização morfológica de um mutante em Eucalyptus - Revolti, Paola Mazza [UNESP] (2015)
Eucalyptus has become one of the most planted forestry genus in the world, because of the use of many commercial products generation. Aiming to increase productivity and introduce desirable traits, forest genetic improvement techniques have been used. However, physiological changes may occur, resulting in loss and delay in improvement programs. The identification and characterization of genes related to diseases and anomalies are important for the forest improvement programs. In a controlled cross of Eucalyptus grandis individuals, the Suzano Papel and Celulose SA company has detected an anomaly with Mendelian segregation ratio of 3:1 (normal:abnormal) in the progeny. The abnormal plants showed notable changes in its external morphology, and early death of individuals. Previous studies have identified a molecular mark related to the anomaly, but no morphological and anatomical study was performed to compare the abnormal plants with the functions of the identified genes. In this way, the aim of this study was morphoanatomical analysis of normal and abnormal materials in the initial stage of development and evaluate phenotypic morphological characteristics in search of differential patterns in mutant plants. For this, samples were evaluated using conventional techniques in plant anatomy and scanning electron microscopy. The young plants of Eucalyptus, normal and anomalous showed morphological differences. The anomalous plants were 3 times smaller in height than the normal plants and presented a very branched stems. In normal plants, the stem showed higher cortical area and vascular system more developed and organized. In anomalous plants, the vascular tissues are less developed and with collapsed aspect. The leaf blades from normal plants showed elliptical shape and slightly sinuous contour; already in the anomalous plants, the leaf blade showed very irregular contour. More developed stipules were observed associated with the leaves of the ...